The Impact of Innovation on Leadership Succession in Family Businesses: A Structured Literature Review [2004-2024] - Bahmann, Benjamin; Carbon, Claus-Christian (European Journal of Family Business, 2025)
This study delves into the intricate relationship between innovation and leadership succession in family businesses. To achieve this, we conducted a systematic literature review of 36 articles spanning 2004 to 2024, with the aim of identifying key themes and research gaps. The review revealed a notable lack of integration between leadership succession and innovation. Moreover, the review allowed us to identify five key research areas—entrepreneurship, knowledge management, performance, succession management, and product and process development—providing a structured framework to examine the complex interplay between these two factors. Although innovation is a recurring topic in the literature, it is rarely linked explicitly to leadership succession and succession decisions. Consequently, this study underscores the need for further research to elucidate the specific impact of innovation on leadership succession. Future investigations should address issues such as the effect of innovation on succession decisions, gender differences in innovation and succession, and the role of intergenerational knowledge transfer, as these could provide valuable insights for family businesses. Additionally, the study outlines practical recommendations to assist both predecessors and successors in navigating this complex landscape. Key suggestions include promoting robust succession planning, cultivating an innovation-driven culture, and facilitating the transfer of practical knowledge—strategies that can foster a successful leadership transition by enhancing a firm’s capacity to innovate and adapt to change.